Influência do teor de cromo e molibdênio na microestrutura e na textura de ligas Fe-Cr-Mo - Moura, Lorena Braga (2010)
The effects of chemical composition on texture and microstructure of five Fe-Cr-Mo alloys with 17%, 15% and 9% chromium contents and 5%, 7% and 9% molybdenum contents were investigated. The thermodynamic study of alloys for all investigated compositions showed the presence of secondary phases such as Mu (μ), Chi (χ), Sigma (σ) and a ferritic matrix. EBSD technique was used to analyze grain size variation and phase precipitation. The intermetallic phases are obstacle to the grain growth of ferritic matrix and grain growth with increasing exposure time. The effect of solution treatment on the microstructure and hardness of alloys revealed lower hardness for solution treated alloys, indicating a single phase ferritic matrix. For tensile test samples containing higher chromium and molybdenum contents, showed higher yield and tensile strengths, with reduced elongation. The influence of chromium and molybdenum levels in the variation of deformation texture for alloys showed that raising chromium content increases the intensity of {111} planes and RD fiber, reducing the intensity of the component {001} <110>. The increase in molybdenum contents intensifies ND fiber, specifically the component {111} <112>, making the RD fiber less intense.